(untitled) - Eyler, Brian (London, 2019)
In The Last Days of the Mekong, Brian Eyler takes us on a revealing tour of the Mekong and those who depend on its resources. He travels from the river's headwaters in China to its delta in Southern Vietnam. Along the way he meets the region's diverse peoples, from villagers to community leaders to politicians and policymakers. Through conversations with them, he reveals how China's expansionist policies are drastically--and often literally--reshaping environments. He also highlights the work being done by locals and international groups to save the Mekong and its fragile ecosystem. Eyler makes the case that there are environmentally-sound solutions, but argues these can only come about from serious cooperation and an increased pressure from the international community
Keywords: Economic development.,Mekong River.,Sông Mekong; Phát triển kinh tế